Species-specific hydrocarbon profiles of South African fig wasp communities (Hymenoptera : Chalcidoidea) - Van der Merwe, Julia Frances (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2015.